Solution of Adapting Creative Accounting Practices: An In depth Perception Gap Analysis among Accountants and Auditors of Listed Companies - Asif, Mahbub Karim; Junaid, M. Shaikh; Hock, Oo Yu; Md. Rafiqul, Islam (2016)
Creative Accounting, also known as cosmetic accounting or window dressing, are accounting applications whereby accountants may take advantage of the loopholes in the accounting policies according to the International Accounting Standards (IAS), Generally Accepted Accounting Principles (GAAP). Auditors may also overlook such practices, as they are not considered fraudulent. The concerned parties involved takes advantage of the accounting policy loopholes to make a lucrative financial statement. This research is conducted on the empirical data collected from the auditors and the accountants of the listed companies in Bangladesh to determine the solution of adapting Creative Accounting practices among accountants and auditors. Solution to this practice can be achieved by imposing punitive measures by national bodies, introducing forensic accounting practice, and forensic cell to monitor the practices and compliance, giving emphasis to ethical code of accounting practice, and creating mass awareness among the investors regarding its practice.